2011
DOI: 10.1016/j.mrfmmm.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular microRNA: A new source of biomarkers

Abstract: MicroRNAs (miRNAs) are a recently discovered class of small, non-coding RNAs that regulate protein levels post-transcriptionally. miRNAs play important regulatory roles in many cellular processes, including differentiation, neoplastic transformation, and cell replication and regeneration. Because of these regulatory roles, it is not surprising that aberrant miRNA expression has been implicated in several diseases. Recent studies have reported significant levels of miRNAs in serum and other body fluids, raising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
449
1
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(464 citation statements)
references
References 72 publications
1
449
1
13
Order By: Relevance
“…Previous studies have reported that certain miRNAs may be used as biomarkers for the diagnosis and prognosis of breast cancer and various diseases (25,26). As compared with conventional protein-based biomarkers, certain miRNAs have several potential advantages, including easy detection by PCR, relative homogeneity and highly specific expression profiles (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that certain miRNAs may be used as biomarkers for the diagnosis and prognosis of breast cancer and various diseases (25,26). As compared with conventional protein-based biomarkers, certain miRNAs have several potential advantages, including easy detection by PCR, relative homogeneity and highly specific expression profiles (25).…”
Section: Discussionmentioning
confidence: 99%
“…19 Therefore, we next measured the levels of circulating tRNA and its derivatives using an anti-m1A antibody-based ELISA. 11 This ELISA assay detects tRNA (unfolded), tRNA-derived fragments (e.g., tiRNA), and mononucleoside free m1A (summarized in Figure 7).…”
Section: The Visualization and Quantification Of Trna Conformational mentioning
confidence: 99%
“…The sequences of the majority of miRNAs are conserved among different species and their expression is tissue-or biological stage-specific (20). miRNAs are accessible through non-invasive methods, and can be easily assessed by sensitive and specific methods such as quantitative polymerase chain reaction (qPCR) (19,20).…”
Section: Introductionmentioning
confidence: 99%